In the name of the people: left populists versus right populists. Issue 1 (1st January 2020) - Rama, José; Santana, Andrés
ABSTRACT: Using the 8th Round of the European Social Survey, we analyse the electoral competition between left-wing (LWPPs) and right-wing populist parties (RWPPs) in the six European countries where this type of competition has occurred (France, Germany, Iceland, Italy, Lithuania and The Netherlands). By focusing on the competition between populist parties in the same sample of countries we can resolve what tells apart a LWPP voter from a RWPP voter. Thus, we study the factors that explain their different voting behaviour and confine our attention to the four main factors that affect populist competition: anti-elite attitudes, material deprivation, euro-scepticism and anti-immigration attitudes. Our results show that LWPPs and RWPPs voters are similar in their attitudes towards immigration and the European Union (EU) but differ in their attitudes towards elites and material deprivation.